Exploring the effects of service quality on customer loyalty: An empirical study of Vinaphone - Tran, Dang Khoa; Nguyen, Hoang Son (Journal of Finance - Marketing Research, 2023)
This study was conducted to determine the service quality factors affecting customer loyalty to Vinaphone mobile services in Vietnam. Based on the survey results of 250 customers who have participated in using Vinaphone’s mobile services, the collected data is processed by the SPSS 25.0 software, including descriptive statistics, and the reliability test of the scale measured by Cronbach’s Alpha method, exploratory factor analysis (EFA), analysis of multiple linear regression models. The results after analyzing the data identified five factors of service quality that affect customer loyalty in descending order: call quality, convenience, value-added services, customer support services, and reliability. Based on the research results, five management implications have been proposed to help Vinaphone’s network improve customer loyalty through improving service quality.